2010
DOI: 10.1002/cncr.25734
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐induced osteosarcomas of the calvarium and skull base

Abstract: BACKGROUND: Although a rare complication of ionizing radiation, radiation-induced osteosarcoma is now more frequently recognized as radiation therapy has become common and cancer survival has increased. To date, publications on radiation-induced osteosarcoma of the cranium are limited to a few small series and case reports. METHODS: Data from 175 patients with a history of sarcoma of the head at The University of Texas M. D. Anderson Cancer Center from 1975 to 2007 were reviewed to identify patients with radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…4,9,12,15,18,22,24,27,33,41,42,45,46,50,52,56,58,62,64,66 Nine cases of cranial osteosarcoma secondary to prior therapeutic radiation have been reported in children, 2 involving tumors of the skull base and 7 involving tumors of the calvaria. 8,15,16,33,39,54,55 Four cases of metastatic cranial osteosarcoma have been reported: 3 cases of metastatic cranial osteosarcoma from primary long bone tumors (2 involving the calvaria and 1 involving the cranial base) 40,42,44 and 1 case of metastatic osteosarcoma to the cranial base with a history of radiotherapy, in the context of multifocal disease. 55 The mean age of the pediatric patients with cranial osteosarcoma was 12.2 years and was similar in patients with calvarial and skull base tumors (12.6 and 11.6 years, respectively).…”
Section: Previously Reported Pediatric Cases Of Cranial Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…4,9,12,15,18,22,24,27,33,41,42,45,46,50,52,56,58,62,64,66 Nine cases of cranial osteosarcoma secondary to prior therapeutic radiation have been reported in children, 2 involving tumors of the skull base and 7 involving tumors of the calvaria. 8,15,16,33,39,54,55 Four cases of metastatic cranial osteosarcoma have been reported: 3 cases of metastatic cranial osteosarcoma from primary long bone tumors (2 involving the calvaria and 1 involving the cranial base) 40,42,44 and 1 case of metastatic osteosarcoma to the cranial base with a history of radiotherapy, in the context of multifocal disease. 55 The mean age of the pediatric patients with cranial osteosarcoma was 12.2 years and was similar in patients with calvarial and skull base tumors (12.6 and 11.6 years, respectively).…”
Section: Previously Reported Pediatric Cases Of Cranial Osteosarcomamentioning
confidence: 99%
“…38 Tumors arising secondary to a pathological process are typically more aggressive and have higher recurrence rates than those arising de novo. 54,59 Malignancy resulting from these predisposing factors is also more likely to appear at a more advanced age, 32 contributing to the low incidence of cranial osteosarcoma in the pediatric population. 32,33,59 Traumatic injury has also been implicated in the development of osteosarcoma.…”
mentioning
confidence: 99%
“…At a first glance, the cytologic differential diagnoses of the present case showing highly pleomorphic cells and an abundant chondromyxoid matrix as well as a necrotic dirty background are as follows: glioblastoma, gliosarcoma, chondrosarcoma, chondroblastic osteosarcoma, other dedifferentiated primary or metastatic sarcoma [6,7,8,9,10,11]. The differential diagnosis from other more commonly encountered CNS tumors may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier literature characterises postradiation bone sarcomas much better than their soft-tissue counterparts because of their more common occurrence in the era of orthovoltage radiotherapy, since this frequency is absorbed more quickly by bone than by soft tissues 9. A wide range of therapeutic doses (8 to >60 Gy) have been reported to result in a postradiation sarcoma9; the majority of cases received a median of about 50 Gy 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of therapeutic doses (8 to >60 Gy) have been reported to result in a postradiation sarcoma9; the majority of cases received a median of about 50 Gy 9 10. In a review of secondary malignancies after Ewing's sarcoma, Kuttesh et al found no secondary sarcomas in patients receiving <48 Gy, compared to an absolute risk of 130 cases per 10 000 person-years of observation among patients who had received ≥60 Gy, suggesting dose dependence 9–12…”
Section: Introductionmentioning
confidence: 99%